Hard coat film and its manufacturing method

By introducing alkylated silane derivatives and epoxy hydroxy groups of specific chain lengths into the hard membrane film material, and combining with photoelectrochemical polymerization catalysts, the problem of difficult balance of surface hardness and flexibility of hard membrane film materials in the prior art is solved, and a good balance between high surface hardness and flexibility is achieved, while improving blocking resistance and color transparency.

JP7649170B2Active Publication Date: 2025-03-19KANEKA CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021039985
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-12
Publication Date
2025-03-19
Estimated Expiration
2041-03-12

AI Technical Summary

Technical Problem

The existing hard film materials are difficult to balance the surface hardness and flexibility, and are prone to shrinkage during the UV photocuring process, resulting in cracks and blockage problems.

Method used

Using a hard membrane film material composed of alkylated silane derivatives of specific chain lengths, a specific structure between epoxy hydroxyl groups and silicon atoms is introduced into the hard membrane film layer, combined with a photoelectrostatic polymerization catalyst, a balance of high surface hardness and flexibility is achieved, while reducing the residual amount of epoxy hydroxyl groups through heat treatment and improving blocking resistance.

Benefits of technology

A good balance of surface hardness and flexibility of hard film materials is achieved, while avoiding shrinkage and cracking problems during UV photocuring, improving blocking resistance and color transparency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649170000001
    Figure 0007649170000001
  • Figure 0007649170000002
    Figure 0007649170000002
  • Figure 0007649170000003
    Figure 0007649170000003
Patent Text Reader

Abstract

To provide a hard coat film which is excellent in balance between blocking resistance and colorless transparency while having high surface hardness and flexibility and uses a cured product of a composition of a polyorganosiloxane compound as a hard coat layer, and a method for producing the hard coat film.SOLUTION: The hard coat film comprises: a hard coat layer which is a cured product of a composition of a condensate of a silane compound having a specific structure; and a transparent resin film. The YI of the hard coat film is 2.1 or less, and the hard coat layer of the hard coat film does not cause blocking.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard coat film having a hard coat layer obtained by curing a composition containing a condensate of a specific silane compound on a transparent resin substrate, and a method for producing the same. [Background technology]

[0002] With the rapid progress of electronic devices such as displays, touch panels, and solar cells, there is a demand for devices to be thinner, lighter, and more flexible. In response to these demands, the replacement of glass materials used in substrates, cover windows, etc. with plastic film materials is being considered. For these applications, the plastic films are required to have high heat resistance, dimensional stability at high temperatures, and high mechanical strength. In recent years, curved displays and foldable displays (flexible displays, foldable displays) have been developed. The cover windows of these displays require not only surface hardness and colorless transparency, but also excellent flexibility (flex resistance).

[0003] Since ordinary plastic film materials do not have a sufficiently high surface hardness, a hard coat film made of a hard-coated plastic film is used for the cover window. As a material for forming the hard coat layer in the hard coat film, Patent Document 1 discloses a UV acrylic monomer, and Patent Document 2 discloses a polyorganosilsesquioxane resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-69197 A [Patent Document 2] JP 2019-143161 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, hard coat films using UV acrylic monomers still do not have sufficient surface hardness. If the hard coat layer is made thick or multifunctional in order to improve the surface hardness, there are problems such as increased cure shrinkage of the material during UV curing, which makes the film prone to cracking, and reduced flexibility.

[0006] In addition, the hard coat film using the polyorganosilsesquioxane resin disclosed in Patent Document 2 does not have a sufficient balance between surface hardness and flexibility for use in a cover window. In particular, when the hard coat layer is folded with the hard coat layer facing outward, the hard coat film may be easily cracked.

[0007] As a material for solving these problems, the present inventors have discovered that a hard coat film having a hard coat layer made of a cured product of a polyorganosiloxane compound composition having a polysiloxane structure containing an epoxy group, in which a substituted or unsubstituted hydrocarbon group having a specific chain length is provided between the epoxy group and a silicon atom in the polysiloxane structure, has an excellent balance between surface hardness and flexibility.

[0008] However, this hard coat film sometimes becomes discolored during curing, resulting in an increase in yellowness index (hereinafter, referred to as YI). Furthermore, hard coat films that are not colored upon curing can sometimes cause blocking due to the tackiness of the hard coat surface.

[0009] Therefore, an object of the present invention is to provide a hard coat film having a hard coat layer made of a cured product of a polyorganosiloxane compound composition that has high surface hardness and flexibility while being excellent in balance between blocking resistance and colorless transparency. [Means for solving the problem]

[0010] As a result of intensive research, the present inventors have come to overcome the above-mentioned problems by providing the following configuration.

[0011] 1) A hard coat film comprising a hard coat layer which is a cured product of a condensation composition of a silane compound represented by the following general formula (1) and a transparent resin film, The YI of the hard coat film is 2.1 or less, The hard coat layer of the hard coat film was fixed on a horizontal table with the hard coat side facing up, and a 125 μm thick PET film with an arithmetic mean surface roughness Ra of 20 nm and a maximum height Rz of 500 nm was placed on top of it and subjected to a pressure of 4 kgf / cm 2 A hard coat film characterized in that when a pressure of R is applied in the vertical direction to a 125 μm thick PET film and the PET film is moved in the in-plane direction, the PET film slides smoothly against the hard coat film. (In the formula (1), R 1 is a substituted or unsubstituted alkylene group having 4 to 16 carbon atoms, R 2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and R 3 is a hydrogen atom or a monovalent hydrocarbon group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, x is an integer of 2 or 3, and Y is an epoxy group represented by formula (2). [ka] [ka]

[0012] 2) The hard coat film according to 1), characterized in that the molar ratio of the constitutional unit represented by the following general formula (3) and the constitutional unit represented by the following general formula (4) contained in the cured product [constituent unit represented by general formula (3)] / [constituent unit represented by general formula (4)] is less than 5. (In general formula (3), R 1 and Y are the same as those in the general formula (1). In the general formula (4), R1 and Y are the same as those in general formula (1), and Z is a group selected from a hydrogen atom or an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms.) [ka] [ka]

[0013] 3) The hard coat film according to 1) or 2), wherein the hard coat layer contains a neutral salt catalyst in an amount of 1 ppm to 10,000 ppm.

[0014] 4) The hard coat film according to any one of 1) to 3), wherein the hard coat layer contains an anionic component of a photocationic polymerization initiator.

[0015] 5) The hard coat film according to any one of 1) to 4), wherein the amount of epoxy groups remaining in the cured product and derived from the condensate of the silane compound before curing is 7% or less.

[0016] 6) A hard coat film comprising the hard coat layer according to any one of 1) to 5) above on at least one surface of a transparent resin film, the hard coat film having a total thickness of 10 to 500 μm and a total light transmittance of 80% or more.

[0017] 7) The hard coat film according to 6), wherein the hard coat layer has a thickness of 0.5 to 100 μm.

[0018] 8) The hard coat film according to any one of 1) to 7), wherein the transparent resin film is made of a resin material selected from the group consisting of polyester, polycarbonate, polyamide, polyimide, cyclic polyolefin, acrylic resin, and cellulose-based resin.

[0019] 9) The hard coat film according to any one of 1) to 8), wherein the transparent resin film is a transparent film made of polyethylene terephthalate or a polyimide resin.

[0020] 10) The hard coat film according to 8) or 9), wherein the transparent resin film is a transparent film made of a polyimide resin having an acid dianhydride-derived structure and a diamine-derived structure, the polyimide resin containing an ester group and being soluble in methylene chloride.

[0021] 11). A display comprising the hard coat film according to any one of 1) to 10).

[0022] 12) A method for producing a hard coat film, comprising the steps of: applying a composition containing a condensate of a silane compound represented by general formula (1) and a photocationic polymerization initiator to a transparent resin film; A step of irradiating with active energy rays; A method for producing a hard coat film, comprising the steps of: heating the film to 60° C. or higher in the order given; (wherein, in formula (1), R 1 is a substituted or unsubstituted alkylene group having 4 to 16 carbon atoms, R 2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and R 3 is a hydrogen atom or a monovalent hydrocarbon group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, x is an integer of 2 or 3, and Y is an epoxy group represented by general formula (2). [ka] [ka]

[0023] 13) The method for producing a hard coat film according to 12), wherein the step of heating to 60°C or higher comprises heating at a temperature in the range of 60°C to 200°C.

[0024] 14) The method for producing a hard coat film according to 12) or 13), characterized in that the molar ratio of the constitutional unit represented by the following general formula (3) contained in the cured product of the composition containing the silane compound condensate and the photocationic polymerization initiator to the constitutional unit represented by the following general formula (4) [constituent unit represented by general formula (3)] / [constituent unit represented by general formula (4)] is less than 5. (In general formula (3), R 1 and Y are the same as those in the general formula (1). In the general formula (4), R 1 and Y are the same as those in general formula (1), and Z is a group selected from a hydrogen atom or an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms.) [ka] [ka]

[0025] 15) The method for producing a hard coat film according to any one of 12) to 14), characterized in that the hard coat film contains a neutral salt catalyst in an amount of 1 ppm to 10,000 ppm in a cured product of a composition containing a silane compound condensate and a photocationic polymerization initiator.

[0026] 16) The method for producing a hard coat film according to any one of 12) to 15), wherein the hard coat film contains a cured product of a composition containing a silane compound condensate and a cationic photopolymerization initiator and an anionic component of the cationic photopolymerization initiator.

[0027] 17) The method for producing a hard coat film according to any one of 12) to 16), wherein the epoxy groups remaining in the cured product of the composition containing the silane compound condensate and the photocationic polymerization initiator in the hard coat film are 7% or less of the epoxy groups in the silane compound condensate before curing. Effect of the Invention

[0028] According to the present invention, it is possible to provide a hard coat film having a hard coat layer made of a cured product of a polyorganosiloxane compound composition which has high surface hardness and flexibility while exhibiting an excellent balance between blocking resistance and colorless transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] In this specification, the condensation product of the silane compound is also referred to as a polyorganosiloxane compound.

[0030] The hard coat layer of the hard coat film of the present invention is a cured product of a hard coat composition containing a condensate of a silane compound represented by the following general formula (1): In general formula (1), R 1 is a substituted or unsubstituted alkylene group having 4 to 16 carbon atoms, R 2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and R 3 is a hydrogen atom or a monovalent hydrocarbon group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, x is an integer of 2 or 3, and Y is an epoxy group represented by the general formula (2). 2 ) x R 3 3-x Hydrolyzable silane compounds having the structure have two or three (-OR 2 ) Si-OR 2 Since the silane compound is hydrolyzable, it is condensed to give a condensation product of the silane compound. [ka] [ka]

[0031] The hard coat layer of the hard coat film of the present invention has a polysiloxane structure containing an epoxy group, and is obtained by curing a hard coat composition that contains, as an essential component, a polyorganosiloxane compound that is a condensation product in which a substituted or unsubstituted hydrocarbon group having a specific chain length is provided between the epoxy group and a silicon atom in the polysiloxane structure, and that optionally contains a photocationic polymerization initiator, a reactive diluent, a photosensitizer, particles, a solvent, additives, etc., as described below.

[0032] The condensation product of the silane compound will be described below. [Condensation products of silane compounds (polyorganosiloxane compounds)]

[0033] In general formula (1), R 1 represents a substituted or unsubstituted alkylene group having 4 to 16 carbon atoms. Specific examples of the unsubstituted alkylene group include a tetramethylene group, a pentamethylene group, a hexamethylene group, a heptamethylene group, an octamethylene group, a decamethylene group, a dodecamethylene group, a tetradecamethylene group, and a hexadecamethylene group.

[0034] R 1 may further have a substituent having 1 to 6 carbon atoms, examples of which include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a cyclohexyl group, and a phenyl group.

[0035] R 1 From the viewpoint of flexibility of the cured product, an unsubstituted linear alkylene group is preferred.

[0036] In general formula (1), R 2 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an isopropyl group, an isobutyl group, a cyclohexyl group, and an ethylhexyl group. From the viewpoint of facilitating hydrolysis and condensation of a silane compound having a hydrolyzable silyl group, R 2The alkyl group is preferably a methyl group, an ethyl group or a propyl group, and most preferably a methyl group.

[0037] In general formula (1), R 3 represents a hydrogen atom or a monovalent hydrocarbon group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms. Examples of such hydrocarbon groups include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an isopropyl group, an isobutyl group, a cyclohexyl group, an ethylhexyl group, a benzyl group, a phenyl group, a tolyl group, a xylyl group, a naphthyl group, and a phenethyl group.

[0038] In general formula (1), x is an integer of 2 or 3, and is appropriately selected depending on the various physical properties required for the hard coat.

[0039] Specific examples of the silane compound (1) include 4-glycidyloxybutyltrimethoxysilane, 4-glycidyloxybutylmethyldimethoxysilane, 4-glycidyloxybutyltriethoxysilane, 4-glycidyloxybutylmethyldiethoxysilane, 5-glycidyloxypentyltrimethoxysilane, 5-glycidyloxypentylmethyldimethoxysilane, 5-glycidyloxypentyltriethoxysilane, 5-glycidyloxypentylmethyldiethoxysilane, 6-glycidyloxyhexyltrimethoxysilane, 6-glycidyloxyhexyltrimethoxysilane, 6-glycidyloxyhexyltriethoxy ... Glycidyloxyhexylmethyldimethoxysilane, 6-glycidyloxyhexyltriethoxysilane, 6-glycidyloxyhexylmethyldiethoxysilane, 7-glycidyloxyheptyltrimethoxysilane, 7-glycidyloxyheptylmethyldimethoxysilane, 7-glycidyloxyheptyltriethoxysilane, 7-glycidyloxyheptylmethyldiethoxysilane, 8-glycidyloxyoctyltrimethoxysilane, 8-glycidyloxyoctylmethyldimethoxysilane, 8-glycidyloxyoctyltriethoxysilane , 8-glycidyloxyoctylmethyldiethoxysilane, 9-glycidyloxynonyltrimethoxysilane, 9-glycidyloxynonylmethyldimethoxysilane, 9-glycidyloxynonyltriethoxysilane, 9-glycidyloxynonylmethyldiethoxysilane, 10-glycidyloxydecyltrimethoxysilane, 10-glycidyloxydecylmethyldimethoxysilane, 10-glycidyloxydecyltriethoxysilane, 10-glycidyloxydecylmethyldiethoxysilane, 11-glycidyloxyundecyltrimethoxysilane, 10-glycidyloxydecylmethyldimethoxysilane, 10-glycidyloxydecyltriethoxysilane, 10-glycidyloxydecylmethyldiethoxysilane, Silane, 11-glycidyloxyundecylmethyldimethoxysilane, 11-glycidyloxyundecyltriethoxysilane, 11-glycidyloxyundecylmethyldiethoxysilane, 12-glycidyloxydodecyltrimethoxysilane, 12-glycidyloxydodecylmethyldimethoxysilane, 12-glycidyloxydodecyltriethoxysilane, 12-glycidyloxydodecylmethyldiethoxysilane, 13-glycidyloxytridecyltrimethoxysilane, 13-glycidyloxytridecylmethyldimethoxysilane,13-glycidyloxytridecyltriethoxysilane, 13-glycidyloxytridecylmethyldiethoxysilane, 14-glycidyloxytetradecyltrimethoxysilane, 14-glycidyloxytetradecylmethyldimethoxysilane, 14-glycidyloxytetradecyltriethoxysilane, 14-glycidyloxytetradecylmethyldiethoxysilane, 15-glycidyloxypentadecyltrimethoxysilane, 15-glycidyloxypentadecyltrimethoxysilane, Examples of glycidyl group-containing silanes include 15-glycidyloxypentadecylmethyldimethoxysilane, 15-glycidyloxypentadecyltriethoxysilane, 15-glycidyloxypentadecylmethyldiethoxysilane, 16-glycidyloxyhexadecyltrimethoxysilane, 16-glycidyloxyhexadecylmethyldimethoxysilane, 16-glycidyloxyhexadecyltriethoxysilane, and 16-glycidyloxyhexadecylmethyldiethoxysilane.

[0040] The silane compound condensate contained in the hard coat layer of the present invention has an alkylene group having a specific chain length between the epoxy group and the silicon atom that chemically bonds the epoxy group, and therefore the hard coat film obtained by curing exhibits excellent flexibility. 1 R is preferably an alkylene group having 4 to 16 carbon atoms, more preferably an alkylene group having 6 to 14 carbon atoms, and even more preferably an alkylene group having 8 to 12 carbon atoms. 1 If the number of carbon atoms is 3 or less, the flexibility of the hard coat film may be insufficient, whereas if the number of carbon atoms is 17 or more, the surface hardness of the hard coat film may decrease.

[0041] The weight average molecular weight of the silane compound condensate contained in the hard coat layer of the present invention is preferably 500 or more from the viewpoint of increasing the hardness of the cured product. In addition, from the viewpoint of suppressing the volatilization of the silane compound condensate, the weight average molecular weight of the silane compound condensate is preferably 500 or more. On the other hand, if the molecular weight is too large, it may become cloudy due to a decrease in compatibility with other compositions. Therefore, the weight average molecular weight of the silane compound condensate is preferably 20,000 or less.

[0042] The weight-average molecular weight of the condensate of the silane compound contained in the hard coat layer of the present invention can be controlled by appropriately selecting the amount of water used in the reaction, the type and amount of catalyst.For example, the weight-average molecular weight can be increased by increasing the amount of water initially charged.

[0043] The condensate of the silane compound contained in the hard coat layer of the present invention contains a constitutional unit represented by general formula (3) or general formula (4) formed by hydrolysis and condensation reaction of the silane compound represented by general formula (1). 3 / 2 The structural unit represented by the general formula (4) (hereinafter referred to as [SiO 2 / 2 The ratio of [SiO 3 / 2 body] / [SiO 2 / 2 The number of carbon atoms is not particularly limited, but is preferably less than 5, more preferably 4 or less, and even more preferably 3 or less, and may be 0. 3 / 2 Body and SiO 2 / 2 Body ratio [SiO 3 / 2 body] / [SiO 2 / 2 By making the SiO content in the condensate less than 5, the hard coat film of the present invention exhibits excellent flexibility. 3 / 2 The content of [SiO 3 / 2 body] / [SiO 2 / 2 If the molecular weight ratio is 5 or more, the viscosity of the resulting condensate may become so high that molding into a hard coat film becomes difficult, or the hard coat film may have a dense structure, resulting in a decrease in flexibility. [ka] [ka]

[0044] In general formula (3), R 1 and Y are the same as those in general formula (1).

[0045] In general formula (4), R 1 and Y are the same as those in general formula (1).

[0046] In general formula (4), Z represents a group selected from a hydrogen atom or an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms. Examples of such groups include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentyloxy group, a hexyloxy group, a heptyloxy group, an octyloxy group, a nonyloxy group, a decyloxy group, a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an isopropyl group, an isobutyl group, a cyclohexyl group, an ethylhexyl group, a benzyl group, a phenyl group, a tolyl group, a xylyl group, a naphthyl group, and a phenethyl group.

[0047] The SiO in the polyorganosiloxane compound contained in the hard coat layer of the present invention 3 / 2 Body and SiO 2 / 2 The content and proportion of the body, e.g. 29 It can be calculated by Si-NMR measurement. 29 In the Si-NMR measurement, SiO 3 / 2 Chemical shift of silicon atom in the body and SiO 2 / 2 The chemical shifts of silicon atoms in the body are different and show signals at different positions in the spectrum. Therefore, the integral value of each signal is calculated to obtain the above ratio [SiO 3 / 2 body] / [SiO 2 / 2 body] can be sought.

[0048] In addition, the SiO 3 / 2 Body and SiO 2 / 2 Body ratio [SiO 3 / 2 body] / [SiO 2 / 2 The ratio [SiO 2 ] can be controlled by appropriately selecting the amount of water and the type and amount of catalyst used in the reaction. For example, the amount of catalyst initially charged can be increased to control the ratio [SiO 2 ]. 3 / 2 body] / [SiO 2 / 2 body] can be made larger.

[0049] [SiO 3 / 2 The compound is a silane compound having three alkoxy groups (Si-OR) in which x=3 in the general formula (1). 2 ) have all undergone a condensation reaction to form Si-O-Si bonds. [SiO 2 / 2 The silane compound having x=2 or 3 in the general formula (1) has two or three alkoxy groups, of which two undergo a condensation reaction to form a Si-O-Si bond.

[0050] The condensation product of a silane compound having an epoxy group in the molecule represented by the general formula (1) [SiO 3 / 2 body] / [SiO 2 / 2 In the case of curing with an acid generated from a photocationic polymerization initiator, the [SiO 3 / 2 body] / [SiO 2 / 2 The condensation product of the silane compound having an epoxy group in the molecule represented by the general formula (1) before curing, [SiO 3 / 2 body] / [SiO 2 / 2 body] is almost the same.

[0051] The amount of water required for hydrolysis and condensation reactions is determined by the amount of OR bound directly to silicon atoms. 2 Group (OR in general formula (1) 2 The amount of water is preferably 0.3 to 3 equivalents, more preferably 0.5 to 2 equivalents, per equivalent of the OR group. 2If the amount exceeds 3 equivalents, the reaction rate of the hydrolysis and condensation reaction will be too high, resulting in the formation of high molecular weight condensates, which may reduce the physical properties and transparency of the cured film.

[0052] The OR remaining in the condensate of the silane compound contained in the hard coat layer of the present invention 2 The number of groups in one molecule of the silane compound condensate is preferably 2 or less, more preferably 1 or less, even more preferably 0.5 or less, particularly preferably 0.1 or less, and most preferably none remain.

[0053] From the viewpoint of increasing the density of crosslinking points and improving the hardness of the cured product, it is preferable that the residual rate of the epoxy structure-containing group in the condensate of the silane compound obtained by hydrolysis and condensation of the silane compound represented by general formula (1) is high.

[0054] The residual ratio of the epoxy structure-containing group, that is, the ratio of the number of moles of the epoxy structure-containing group in the polyorganosiloxane compound obtained by condensation to the number of moles of the epoxy structure-containing group in the raw material silane compound (1), is preferably 20% or more, more preferably 40% or more, and even more preferably 60% or more. 1 It can be calculated by H-NMR measurement.

[0055] In the present invention, the hydrolysis and condensation reaction can be carried out in the presence of any one of an acid catalyst, a basic catalyst, and a neutral salt catalyst. From the viewpoint of suppressing deactivation due to ring opening of the epoxy group during the condensation reaction, a basic catalyst or a neutral salt catalyst is preferred. 3 / 2 Body and SiO 2 / 2 Body ratio [SiO 3 / 2 body] / [SiO 2 / 2In order to reduce the size of the reaction system, it may be preferable to use a neutral salt catalyst. By carrying out the hydrolysis and condensation reaction in the presence of a neutral salt catalyst, the SiO 2 in the condensate of the silane compound can be reduced without deactivating the epoxy groups before and after the hydrolysis and condensation reaction and during storage. 3 / 2 Body and SiO 2 / 2 Body ratio [SiO 3 / 2 body] / [SiO 2 / 2 It is possible to obtain a condensation product of a silane compound having a small molecular weight.

[0056] In addition, the neutral salt catalyst itself does not damage the manufacturing or storage containers, so it can be used without restrictions on the materials of the manufacturing or storage equipment. This is because, in general, acid and base catalysts themselves react electrophilically or nucleophilically with various substances, and by changing the hydrogen ion or hydroxide ion concentration in the reaction solution, these ions contribute to the reaction, whereas neutral salts have extremely low reaction activity as described above.

[0057] In addition, when an acid catalyst or a base catalyst is used in the hydrolysis and condensation reactions, it is necessary to go through an acid / base removal step or a neutralization step for the above reasons. These steps are undesirable because they are cumbersome and reduce the yield. In terms of these problems, the use of a neutral salt catalyst is preferable because it does not require these steps.

[0058] The neutral salt used in the present invention refers to a normal salt consisting of a strong acid and a strong base, and is a salt consisting of a combination of a cation selected from the group consisting of Group 1 element ions and Group 2 element ions, and an anion selected from the group consisting of chloride ions, bromide ions, and iodide ions.

[0059] Specific examples of neutral salts in the present invention include lithium chloride, sodium chloride, potassium chloride, beryllium chloride, magnesium chloride, calcium chloride, lithium bromide, sodium bromide, potassium bromide, beryllium bromide, magnesium bromide, calcium bromide, lithium iodide, sodium iodide, potassium iodide, beryllium iodide, magnesium iodide, and calcium iodide.

[0060] In the present invention, the greater the amount of neutral salt used, the more the hydrolysis and condensation reaction of the silane compound is promoted. However, when the transparency of the condensate and the purification process are taken into consideration, the smaller the amount added, the better.

[0061] The amount of the neutral salt used in the present invention is preferably 0.000001 mol or more and 0.1 mol or less, particularly preferably 0.000005 mol or more and 0.01 mol or less, relative to 1 mol of the hydrolyzable silyl group of the silane compound. The amount of the neutral salt (catalyst) remaining in the polyorganosiloxane compound is preferably 1 ppm to 10,000 ppm, more preferably 50 ppm to 5,000 ppm, and even more preferably 100 ppm to 1,000 ppm.

[0062] In the production of the condensate of the silane compound contained in the hard coat layer of the present invention, it is preferable to carry out the production while refluxing the dilution solvent, alcohol generated by hydrolysis, etc., in consideration of safety during production.

[0063] The dilution solvent used in the production of the condensate of the silane compound contained in the hard coat layer of the present invention is preferably a water-soluble alcohol or ether compound.

[0064] The reason for the above is that the silane compound (1) used in the present invention is often poorly compatible with neutral salts and water used for hydrolysis, and therefore it is preferable for the reaction solution to be compatible in order to smoothly proceed with the reaction.

[0065] The boiling point of the dilution solvent used in the production of the silane compound condensate is preferably 40°C or higher and 200°C or lower, more preferably 50°C or higher and 200°C or lower, and even more preferably 60°C or higher and 200°C or lower.

[0066] If the boiling point of the dilution solvent is less than 40°C, the dilution solvent will reflux at low temperatures, slowing down the reaction rate.If the boiling point of the dilution solvent is more than 200°C, the boiling point is too high and it will be difficult to remove the dilution solvent after the reaction, so it may be necessary to incorporate a complicated process such as liquid separation and extraction.

[0067] Specific examples of the diluent solvent used in the production of the silane compound condensate of the present invention include methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, 1-methoxy-2-propanol, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol dimethyl ether, etc. These diluents may be used alone or in combination of two or more.

[0068] The reaction temperature in the production of the silane compound condensate contained in the hard coat layer of the present invention is preferably in the range of 40 to 200°C, more preferably in the range of 50 to 200°C, and further preferably in the range of 60 to 200°C.

[0069] If the reaction temperature is lower than 40°C, the catalytic activity of the neutral salt decreases, tending to significantly increase the reaction time. If the reaction temperature is higher than 200°C, there is a concern that the organic functional groups may undergo side reactions and become inactivated.

[0070] When a silane compound condensation product is obtained by condensation of a silane compound, in addition to the silane compound (1) containing an epoxy group, a silane compound (5) containing no epoxy group represented by the following general formula (5) may be used. (In formula (5), R 4is a monovalent group selected from the group consisting of substituted or unsubstituted alkyl groups having 1 to 10 carbon atoms, alkenyl groups, aryl groups having 6 to 25 carbon atoms, and aralkyl groups having 7 to 12 carbon atoms, which does not contain an epoxy group; R 5 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and R 6 is a monovalent hydrocarbon group selected from a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, and x is an integer of 2 or 3. [ka]

[0071] From the viewpoint of improving the mechanical strength of the hard coat layer in the hard coat film, the number of epoxy groups contained in one molecule of the condensation product of the silane compound is preferably as large as possible. In the reaction of the silane compound, the molar ratio of the silane compound (5) represented by the general formula (5) to the silane compound (1) represented by the general formula (1) is preferably 2 or less, more preferably 1 or less, even more preferably 0.4 or less, and particularly preferably 0.2 or less. The molar ratio of the silane compound (5) represented by the general formula (5) to the silane compound (1) represented by the general formula (1) may be 0.

[0072] The hard coat film of the present invention comprises a hard coat layer obtained by curing a hard coat composition containing a condensate of a silane compound having an epoxy group in the molecule represented by general formula (1) (a composition of the condensate of a silane compound represented by general formula (1)). The hard coat composition will be described below.

[0073] [Hard Coat Composition] The hard coat composition of the present invention is a hard coat composition containing the above-mentioned condensate of a silane compound as an essential component. The hard coat composition of the present invention preferably further contains a photocationic initiator, and may contain other components such as a surface conditioner and a surface modifier.

[0074] From the viewpoint of forming a hard coat layer in a hard coat film having excellent mechanical strength, the content of the silane compound condensate in the hard coat composition is preferably 40 parts by weight or more, more preferably 50 parts by weight or more, and even more preferably 60 parts by weight or more, per 100 parts by weight of the total solid content.

[0075] <Photocationic polymerization initiator> The hard coat composition preferably contains a photocationic polymerization initiator. The photocationic polymerization initiator is a compound (photoacid generator) that generates an acid by irradiation with active energy rays. The acid generated from the photoacid generator promotes a ring-opening reaction and a polymerization reaction of the epoxy group contained in the condensate of the silane compound, forming an intermolecular crosslink, and curing the hard coat composition.

[0076] Examples of photoacid generators include strong acids such as toluenesulfonic acid or boron tetrafluoride; onium salts such as sulfonium salts, ammonium salts, phosphonium salts, iodonium salts, and selenium salts; iron-allene complexes; silanol-metal chelate complexes; sulfonic acid derivatives such as disulfones, disulfonyldiazomethanes, disulfonylmethanes, sulfonylbenzoylmethanes, imide sulfonates, and benzoin sulfonates; and organic halogen compounds.

[0077] Among the above photoacid generators, aromatic sulfonium salts or aromatic iodonium salts are preferred because they have high stability in a hard coat composition containing a condensate of a silane compound having an epoxy group. Among them, aromatic sulfonium salts are preferred from the viewpoint of curability. As counter anions thereof, fluorophosphate-based anions, fluoroantimonate-based anions, fluoroborate-based anions, etc. are listed. Among them, fluorophosphate-based anions and fluoroantimonate-based anions, which have a high curing speed and tend to increase the heat resistance of the cured product, are preferred, and fluorophosphate-based anions are preferred. Counter anions tend to remain in the cured product as the same structure or as residues from which some fluorine atoms have been removed.

[0078] Specific examples of the photoacid generator include diphenyl(4-phenylthiophenyl)sulfonium hexafluorophosphate, hexafluorophosphate derivatives in which some or all of the fluorine atoms of hexafluorophosphate are substituted with perfluoroalkyl groups, triphenylsulfonium tetrakispentafluorophenylborate, and hexafluoroantimonate.

[0079] The content of the photocationic polymerization initiator in the hard coat composition is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 0.2 to 2 parts by weight, based on 100 parts by weight of the condensate of the silane compound.

[0080] <Reactive diluent> The hard coat composition may further contain a cationic curing compound other than the condensate of a silane compound as a reactive diluent. A compound having a cationic polymerizable functional group is used as the reactive diluent for photo-cationic polymerization. Examples of the cationic polymerizable functional group of the reactive diluent include an epoxy group, a vinyl ether group, an oxetane group, and an alkoxysilyl group. Among them, the reactive diluent is preferably one having an epoxy group because it has high reactivity with the epoxy group of the polyorganosiloxane compound of the present invention. In addition, in the hard coat composition of the present invention, the other cationic curing compound as the reactive diluent may be used alone or in combination of two or more.

[0081] The content of the reactive diluent in the hard coat composition is preferably 100 parts by weight or less, and more preferably 50 parts by weight or less, based on 100 parts by weight of the condensate of the silane compound.

[0082] <Photosensitizer> In the hard coat composition, a photosensitizer may be used for the purpose of improving the photosensitivity of the photoacid generator. The photosensitizer is more efficient when it can absorb light in a wavelength range that cannot be absorbed by the photoacid generator used, so it is preferable that the photosensitizer has little overlap with the absorption wavelength range of the photoacid generator.

[0083] The photosensitizer is not particularly limited, but examples thereof include anthracene derivatives, benzophenone derivatives, thioxanthone derivatives, anthraquinone derivatives, and benzoyl derivatives.

[0084] The content of the photosensitizer in the hard coat composition of the present invention is preferably 50 parts by weight or less, more preferably 30 parts by weight or less, and even more preferably 10 parts by weight or less, per 100 parts by weight of the above-mentioned photoacid generator.

[0085] <Particle> The hard coat composition may contain particles for the purpose of adjusting the film properties (surface hardness and flexibility) and suppressing curing shrinkage. As the particles, organic particles, inorganic particles, organic-inorganic composite particles, etc. may be appropriately selected and used. Examples of the organic particle material include poly(meth)acrylic acid alkyl ester, crosslinked poly(meth)acrylic acid alkyl ester, crosslinked styrene, nylon, silicone, crosslinked silicone, crosslinked urethane, crosslinked butadiene, etc. Examples of the inorganic particle material include metal oxides such as silica, titania, alumina, tin oxide, zirconia, zinc oxide, and antimony oxide; metal nitrides such as silicon nitride and boron nitride; and metal salts such as calcium carbonate, calcium hydrogen phosphate, calcium phosphate, and aluminum phosphate. Examples of the organic-inorganic composite filler include those in which an inorganic layer is formed on the surface of organic particles, and those in which an organic layer or organic fine particles is formed on the surface of inorganic particles.

[0086] Examples of the particle shape include spherical, powdery, fibrous, needle-like, scaly, etc. Spherical particles are not anisotropic and are less likely to cause uneven distribution of stress, so that the generation of distortion is suppressed, which can contribute to suppression of warping of the hard coat film caused by cure shrinkage, etc.

[0087] The average particle size of the particles is, for example, about 5 nm to 10 μm. From the viewpoint of increasing the transparency of the hard coat film, the average particle size is preferably 1000 nm or less, more preferably 500 nm or less, even more preferably 300 nm or less, and particularly preferably 100 nm or less. The particle size can be measured by a laser diffraction / scattering type particle size distribution measuring device, and the volume-based median size is taken as the average particle size.

[0088] The hard coat composition may contain surface-modified particles. By surface-modifying particles, the dispersibility of particles in the condensation product of silane compound tends to improve. In addition, when the surface of particles is modified by a polymerizable functional group that can react with epoxy group, the functional group on the surface of particles reacts with the epoxy group of the condensation product of silane compound of the present invention to form chemical crosslinking, so that the film strength and flexibility can be improved.

[0089] Examples of polymerizable functional groups that can react with epoxy groups include vinyl groups, (meth)acrylic groups, hydroxyl groups, phenolic hydroxyl groups, carboxyl groups, acid anhydride groups, amino groups, epoxy groups, and oxetane groups. Among these, epoxy groups are preferred. In particular, particles surface-modified with epoxy groups are preferred because they can form chemical crosslinks between the particles and the siloxane compound during curing of the hard coat composition by photocationic polymerization.

[0090] Examples of particles having reactive functional groups on the surface include surface-modified inorganic particles and core-shell polymer particles. These particles may be used alone or in combination.

[0091] The content of the particles in the hard coat composition is preferably 100 parts by weight or less, and more preferably 50 parts by weight or less, based on 100 parts by weight of the condensate of the silane compound.

[0092] <Solvent> The hard coat composition may or may not contain a solvent. When a solvent is contained, it is preferable that the solvent does not dissolve the transparent resin substrate. The content of the solvent is preferably 500 parts by weight or less, more preferably 300 parts by weight or less, and even more preferably 100 parts by weight or less, relative to 100 parts by weight of the condensate of the silane compound of the present invention. When the condensate of the silane compound of the present invention is liquid in the coating environment, it can be coated without a solvent. Not containing a solvent has the advantage that a process of removing the solvent is not required.

[0093] <Additives> The hard coat composition may contain additives such as inorganic pigments, organic pigments, surface conditioners, surface modifiers, plasticizers, dispersants, wetting agents, thickeners, and defoamers. The hard coat composition may also contain a thermoplastic or thermosetting resin material other than the above-mentioned silane compound condensates. When the silane compound condensates and / or resin materials other than the silane compound condensates have radical polymerizability, the hard coat composition may contain a radical polymerization initiator in addition to the photocationic polymerization initiator.

[0094] The hard coat film of the present invention comprises a hard coat layer obtained by curing a hard coat composition containing a condensate of a silane compound having an epoxy group in the molecule represented by the general formula (1) and a transparent resin film layer. The transparent resin film will be described below.

[0095] [Transparent resin film] The substrate to which the hard coat composition is applied is a transparent resin film. The transparent resin film is a resin film that is transparent when viewed with the naked eye, and has a total light transmittance of preferably 80% or more, more preferably 85% or more, and particularly preferably 88% or more. A high total light transmittance tends to provide excellent visibility when incorporated into a display. The transparent resin film is preferably highly colorless, and preferably has a YI of -3.0 to 3.0. The transparent resin film is preferably less cloudy, and has a haze of preferably 3% or less, more preferably 2% or less, and particularly preferably 1% or less.

[0096] The material of the resin film is not particularly limited, and examples thereof include polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate, polyolefin-based resins such as cyclic olefins, polyamide-based resins, polyimides, polyamideimides, and other polyimide-based resins, urethane-based resins, (meth)acrylic resins such as polymethyl methacrylate, polycarbonate-based resins, cellulose-based resins such as triacetyl cellulose, and silicone-based resins. Among them, from the viewpoint of transparency, polyester-based resins, polycarbonate-based resins, polyamide-based resins, polyimide-based resins, cyclic polyolefin-based resins, (meth)acrylic resins, and cellulose-based resins are preferred, and from the viewpoints of transparency, moist heat resistance, and weather resistance, polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate, polyimide-based resins, and (meth)acrylic resins such as polymethyl methacrylate are preferred, and from the viewpoints of transparency, moist heat resistance, and weather resistance, polyethylene phthalate or polyimide resins are preferred, and polyimide resins are more preferred from the viewpoints of surface hardness and durability against repeated bending. The transparent film may be made of only one type of resin material, or may be made of two or more types of resin materials.

[0097] The polyimide resin is obtained by dehydrating and cyclizing a polyamic acid obtained by reacting a tetracarboxylic dianhydride (hereinafter, sometimes simply referred to as "acid dianhydride") with a diamine. That is, the polyimide resin has a structure derived from an acid dianhydride and a structure derived from a diamine. The polyimide resin preferably contains an alicyclic structure or a fluorine atom in at least one of the acid dianhydride and the diamine, and more preferably contains an alicyclic structure or a fluorine atom in both the acid dianhydride and the diamine.

[0098] The weight-average molecular weight of the polyimide resin is preferably 5,000 to 500,000, more preferably 10,000 to 300,000, and even more preferably 30,000 to 200,000. When the weight-average molecular weight is within this range, sufficient mechanical properties and moldability are likely to be obtained. The molecular weight in this specification is a value calculated as polyethylene oxide (PEO) by gel permeation chromatography (GPC). The molecular weight can be adjusted by the molar ratio of diamine and acid dianhydride, reaction conditions, etc.

[0099] (acid dianhydride) In order to obtain a polyimide resin film having high transparency and little coloration, the polyimide resin preferably contains an alicyclic acid dianhydride and / or a fluorine-containing aromatic acid dianhydride as the acid dianhydride component.

[0100] Examples of the alicyclic acid dianhydride include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, and 1,1'-bicyclohexane-3,3',4,4'-tetracarboxylic-3,4,3',4'-dianhydride. Among them, it is preferable to use 1,2,3,4-cyclobutanetetracarboxylic dianhydride and / or 1,2,4,5-cyclohexanetetracarboxylic dianhydride as the acid dianhydride, and 1,2,3,4-cyclobutanetetracarboxylic dianhydride is particularly preferable, since polyimide having excellent transparency and mechanical strength can be obtained.

[0101] Examples of fluorine-containing aromatic dianhydrides include 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, and 2,2-bis{4-[4-(1,2-dicarboxy)phenoxy]phenyl}-1,1,1,3,3,3-hexafluoropropane dianhydride. Among them, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride is preferred. By using a fluorine-containing aromatic dianhydride as the dianhydride component, the solubility of the polyimide resin in a solvent tends to increase. In the case where the polyimide resin is soluble in a solvent, when the hard coat composition is applied, the surface of the polyimide film may be slightly swollen by the solvent or monomer in the composition, which may improve the adhesion between the polyimide film and the hard coat layer.

[0102] The polyimide resin may contain a component other than the alicyclic acid dianhydride and the fluorine-containing aromatic acid dianhydride as the acid dianhydride component. The acid dianhydride other than the alicyclic acid dianhydride and the fluorine-containing aromatic acid dianhydride may be an aromatic tetracarboxylic acid dianhydride having four carbonyls bonded to one aromatic ring, such as pyromellitic acid dianhydride, 1,2,5,6-naphthalene tetracarboxylic acid dianhydride, and 2,3,6,7-naphthalene tetracarboxylic acid dianhydride; 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride, and 2,2-bis(4-hydroxyphenyl)propane dibenzoate-3,3',4 Examples of aromatic tetracarboxylic acid dianhydrides include aromatic tetracarboxylic acid dianhydrides in which two carbonyl groups are bonded to different aromatic rings, such as 3,3',4,4'-tetracarboxylic acid dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 3,4'-oxydiphthalic anhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic acid dianhydride, and bis(trimellitic anhydride).

[0103] The above-mentioned bis(trimellitic anhydride) ester is an ester of trimellitic anhydride and a diol. The diol is preferably an aromatic diol. Examples of the aromatic diol include hydroquinones, biphenols, and bisphenols. Examples of the bis(trimellitic anhydride) aromatic ester include a compound represented by the following general formula (6). [ka]

[0104] In the general formula (6), n is an integer of 1 or more, and R 7 ~R 10are each independently a hydrogen atom, a fluorine atom, an alkyl group having 1 to 20 carbon atoms, or a perfluoroalkyl group having 1 to 20 carbon atoms. n is an integer of 1 or more. When n is 2 or more, the substituents R 7 ~R 10 may be the same or different.

[0105] Specific examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, a cyclobutyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a cyclopentyl group, an n-hexyl group, a cyclohexyl group, etc. Specific examples of the perfluoroalkyl group include a trifluoromethyl group, etc.

[0106] In the general formula (6), n is preferably 1 or 2, and R 7 ~R 10 are each preferably independently a hydrogen atom, a methyl group, or a trifluoromethyl group. Specific examples of the acid dianhydride in which n=2 in the general formula (6), that is, the bis(trimellitic anhydride) ester having a biphenyl skeleton, include p-biphenylene bis(trimellitic dianhydride) (abbreviation: BP-TME), 3,3'-dimethyl-biphenylene bis(trimellitic dianhydride) (abbreviation: OCBP-TME), and bis(1,3-dioxo-1,3-dihydroisobenzofuran-5-carboxylic acid)-2,2',3,3',5,5'-hexamethylbiphenyl-4,4'diyl (also known as 2,2',3,3',5,5'-hexamethyl-biphenylene bis(trimellitic dianhydride) (abbreviation: TAHMBP)) represented by the following formula (7). A specific preferred example of the acid dianhydride in which n=1 in general formula (1) is p-phenylenebis(trimellitic anhydride) (TMHQ) represented by the following formula (8) can be mentioned. [ka] [ka]

[0107] Polyimides containing a bis(trimellitic anhydride) ester as the acid dianhydride in addition to a fluorine-containing aromatic acid dianhydride tend to exhibit high solubility in low-boiling alkyl halides such as dichloromethane, and the resulting polyimide films tend to exhibit high transparency and mechanical strength.

[0108] (Diamine) The transparent polyimide preferably contains a fluorine-containing aromatic diamine as the diamine component.

[0109] Examples of fluorine-containing aromatic diamines include fluoroalkyl-substituted benzidines in which some or all of the hydrogen atoms of the biphenyl of 4,4'diaminobiphenyl (benzidine) are substituted with fluoroalkyl groups, and fluorine-substituted benzidines in which some or all of the hydrogen atoms of the biphenyl of benzidine are substituted with fluorine atoms. Specific examples of fluorine-containing aromatic diamines include 1,4-diamino-2-fluorobenzene, 1,4-diamino-2,3-difluorobenzene, 1,4-diamino-2,5-difluorobenzene, 1,4-diamino-2,6-difluorobenzene, 1,4-diamino-2,3,5-trifluorobenzene, 1,4-diamino, 2,3,5,6-tetrafluorobenzene, 1,4-diamino-2-(trifluoromethyl)benzene, 1,4-diamino-2,3-bis ... (trifluoromethyl)benzene, 1,4-diamino-2,5-bis(trifluoromethyl)benzene, 1,4-diamino-2,6-bis(trifluoromethyl)benzene, 1,4-diamino-2,3,5-tris(trifluoromethyl)benzene, 1,4-diamino-2,3,5,6-tetrakis(trifluoromethyl)benzene, 2-fluorobenzidine, 3-fluorobenzidine, 2,3-difluorobenzidine, 2,5-difluorobenzidine, 2,6-difluoro 2,3,5-trifluorobenzidine, 2,3,6-trifluorobenzidine, 2,3,5,6-tetrafluorobenzidine, 2,2'-difluorobenzidine, 3,3'-difluorobenzidine, 2,3'-difluorobenzidine, 2,2',3-trifluorobenzidine, 2,3,3'-trifluorobenzidine, 2,2',5-trifluorobenzidine, 2,2',6-trifluorobenzidine, 2,3',5-trifluorobenzidine, 2,3 ',6,-Trifluorobenzidine, 2,2',3,3'-Tetrafluorobenzidine, 2,2',5,5'-Tetrafluorobenzidine, 2,2',6,6'-Tetrafluorobenzidine, 2,2',3,3',6,6'-Hexafluorobenzidine, 2,2',3,3',5,5',6,6'-Octafluorobenzidine, 2-(Trifluoromethyl)benzidine, 3-(Trifluoromethyl)benzidine, 2,3-Bis(trifluoromethyl)benzidine, 2,5-Bis(trifluoromethyl)benzidine, 2,6-bis(trifluoromethyl)benzidine, 2,3,5-tris(trifluoromethyl)benzidine, 2,3,6-tris(trifluoromethyl)benzidine, 2,3,5,6-tetrakis(trifluoromethyl)benzidine, 2,2'-bis(trifluoromethyl)benzidine, 3,3'-bis(trifluoromethyl)benzidine, 2,3'-bis(trifluoromethyl)benzidine, 2,2',3-bis(trifluoromethyl)benzidine, 2,3,3' 2,2',5-tris(trifluoromethyl)benzidine, 2,2',6-tris(trifluoromethyl)benzidine, 2,3',5-tris(trifluoromethyl)benzidine, 2,3',6,-tris(trifluoromethyl)benzidine, 2,2',3,3'-tetrakis(trifluoromethyl)benzidine, 2,2',5,5'-tetrakis(trifluoromethyl)benzidine, 2,2',6,6'-tetrakis(trifluoromethyl)benzidine, etc. are included. From the viewpoint of obtaining a polyimide having excellent transparency and mechanical strength, the fluorine-containing aromatic diamine is preferably a fluoroalkyl-substituted benzidine. Among them, bis(trifluoromethyl)benzidines such as 2,2'-bis(trifluoromethyl)benzidine and 3,3'-bis(trifluoromethyl)benzidine are preferred, and 2,2'-bis(trifluoromethyl)benzidine is particularly preferred.

[0110] By using a sulfonyl group-containing diamine as a diamine component in addition to a fluorine-containing aromatic diamine, the mechanical strength of the polyimide resin tends to improve. Examples of the sulfonyl group-containing diamine include diphenyl sulfone derivatives such as 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, and 4,4'-bis[4-(4-aminophenoxy)phenoxy]diphenyl sulfone. Among these, 3,3'-diaminodiphenyl sulfone (3,3'-DDS) or 4,4'-diaminodiphenyl sulfone (4,4'-DDS) is preferred, with 3,3'-DDS being particularly preferred, since it can improve the mechanical strength of the polyimide resin without impairing the transparency.

[0111] The polyimide resin may contain a component other than the fluorine-containing aromatic diamine and the sulfonyl group-containing diamine as a diamine component. Examples of diamines other than the fluorine-containing aromatic diamine and the sulfonyl group-containing diamine include diamines having two amino groups bonded to one aromatic ring, such as p-phenylenediamine, m-phenylenediamine, and o-phenylenediamine; aromatic diamines having amino groups bonded to different aromatic rings, such as diaminodiphenylether, diaminodiphenylsulfide, diaminobenzophenone, diaminodiphenylalkane, and bis(aminobenzoyl)benzene; and alicyclic diamines, such as diaminocyclohexane and isophoronediamine.

[0112] (Specific example 1 of polyimide composition) In one embodiment, the polyimide resin contains, as the acid dianhydride, an alicyclic acid dianhydride and a fluorine-containing aromatic acid dianhydride, and, as the diamine, a fluorine-containing diamine and a sulfonyl group-containing diamine.

[0113] From the viewpoint of transparency of the polyimide resin, the total of the alicyclic dianhydride and the fluorine-containing aromatic dianhydride is preferably 70 mol% or more in the total amount of 100 mol% of the dianhydride components. The total of the alicyclic dianhydride and the fluorine-containing aromatic dianhydride in the total amount of 100 mol% of the dianhydride components may be 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, or 95 mol% or more. By using an aromatic tetracarboxylic acid dianhydride having two carbonyl groups bonded to each of different aromatic rings in addition to the alicyclic dianhydride and / or the fluorine-containing aromatic dianhydride as the dianhydride component, the heat resistance and mechanical strength may be improved without impairing the transparency of the polyimide resin.

[0114] From the viewpoint of achieving both transparency and mechanical strength and bending resistance of the polyimide resin, the content of the alicyclic dianhydride is preferably 20 to 95 mol% out of the total amount of 100 mol% of the dianhydride components. The content of the alicyclic dianhydride out of the total amount of 100 mol% of the dianhydride components may be 25 mol% or more, 30 mol% or more, 35 mol% or more, 40 mol% or more, 45 mol% or more, or 50 mol% or more. The content of the alicyclic dianhydride out of the total amount of 100 mol% of the dianhydride components may be 90 mol% or less, 85 mol% or less, 80 mol% or less, 75 mol% or less, 70 mol% or less, or 65 mol% or less. Since a polyimide resin having excellent transparency and mechanical strength, as well as excellent bending resistance and adhesion to a hard coat layer can be obtained, the content of 1,2,3,4-cyclobutanetetracarboxylic dianhydride is preferably in the above range.

[0115] From the viewpoint of transparency and flexibility of the polyimide resin, the content of the fluorine-containing aromatic dianhydride may be 5 mol% or more, 10 mol% or more, 15 mol% or more, 20 mol% or more, or 25 mol% or more in the total amount of the dianhydride components (100 mol%). Since a polyimide resin having excellent transparency can be obtained, the content of 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride is preferably in the above range.

[0116] From the viewpoint of transparency of the polyimide resin, the content of the fluorine-containing aromatic diamine may be 25 mol% or more, 30 mol% or more, 35 mol% or more, 40 mol% or more, 45 mol% or more, 50 mol% or more, 55 mol% or more, or 60 mol% or more in the total amount of the diamine components (100 mol%). Since a polyimide resin having excellent transparency can be obtained, it is preferable that the content of 2,2'-bis(trifluoromethyl)benzidine is in the above range.

[0117] From the viewpoint of improving the transparency and mechanical strength of the polyimide resin, the content of the sulfonyl group-containing diamine in the total amount of 100 mol% of the diamine components of the polyimide is preferably 10 to 75 mol%. The content of the sulfonyl group-containing diamine in the total amount of 100 mol% of the diamine components of the polyimide may be 15 mol% or more, 20 mol% or more, or 25 mol% or more. The content of the sulfonyl group-containing diamine in the total amount of 100 mol% of the diamine components of the polyimide may be 70 mol% or less, 65 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, 45 mol% or less, 40 mol% or less, or 35 mol% or less. In particular, it is preferable that the content of 3,3'-DDS is in the above range.

[0118] From the viewpoint of transparency of the polyimide resin, the total of the fluorine-containing aromatic diamine and the sulfonyl group-containing diamine is preferably 70 mol% or more in the total amount of 100 mol% of the diamine components. The total of the fluorine-containing aromatic diamine and the sulfonyl group-containing diamine in the total amount of 100 mol% of the diamine components may be 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, or 95 mol% or more. In particular, the total of the fluoroalkyl-substituted benzidine and 3,3'-DDS in the total amount of 100 mol of the diamine components is preferably within the above range.

[0119] (Specific example 2 of polyimide composition) In one embodiment, the polyimide resin contains the acid dianhydride (trimellitic anhydride ester) represented by the above general formula (6) as the acid dianhydride, and contains a fluorine-containing diamine as the diamine. This polyimide exhibits high solubility in low-boiling alkyl halides such as methylene chloride, and the polyimide film tends to exhibit high transparency and mechanical strength.

[0120] From the viewpoint of transparency and solubility of the polyimide resin, the amount of the acid dianhydride represented by the general formula (6) is preferably 10 to 65 mol%, more preferably 15 to 60 mol%, and more preferably 20 to 50 mol% out of the total amount of the acid dianhydride components (100 mol%). Among the acid dianhydrides represented by the general formula (6), TAHMBP and TMHQ are preferred, and the total of TAHMBP and TMHQ is preferably in the above range.

[0121] When the content of the acid dianhydride represented by general formula (6) is 10 mol % or more, the pencil hardness and elastic modulus of the polyimide film tend to be high, and when the content of the acid dianhydride represented by general formula (6) is 65 mol % or less, the transparency of the polyimide film tends to be high.

[0122] The acid dianhydride component may contain a fluorine-containing aromatic acid dianhydride. In the total amount of the acid dianhydride components (100 mol%), the content of the fluorine-containing aromatic acid dianhydride is preferably 30 to 80 mol%, more preferably 35 to 75 mol%, and even more preferably 45 to 75 mol%. If the content of the fluorine-containing aromatic acid dianhydride is 30 mol% or more, the transparency of the polyimide film tends to be high, and if it is 80 mol% or less, the pencil hardness and elastic modulus of the polyimide film tend to be high.

[0123] In the total amount of the diamine components (100 mol%), the amount of the fluorine-containing diamine is preferably 40 to 100 mol%, more preferably 60 to 80 mol%. In order to obtain a polyimide resin having excellent transparency, it is preferable that the content of the fluoroalkyl-substituted benzidine is in the above range, and in particular, it is preferable that the content of 2,2'-bis(trifluoromethyl)benzidine is in the above range.

[0124] The diamine component may contain 60 mol % or less of a sulfonyl group-containing diamine in addition to the fluorine-containing diamine. As the sulfonyl group-containing diamine, 3,3'DDS is preferred, and the content of 3,3'-DDS is preferably 20 to 40 mol %.

[0125] By using the above-mentioned combination of acid dianhydride and diamine and setting the amount of each acid dianhydride component and diamine component within the above-mentioned range, it is possible to obtain a polyimide that has high solubility in low-boiling point solvents such as methylene chloride, can easily reduce the amount of residual solvent, and is excellent in transparency and mechanical strength.

[0126] (Synthesis of polyamic acid) Polyamic acid is obtained, for example, by reacting an acid dianhydride with a diamine in an organic solvent. It is preferable to use approximately equimolar amounts of the acid dianhydride and the diamine (molar ratio of 95:100 to 105:100). In order to suppress ring-opening of the acid dianhydride, it is preferable to add the acid dianhydride after dissolving the diamine in a solvent. When adding multiple types of diamines or multiple types of acid dianhydrides, they may be added at once or in multiple portions. The polyamic acid solution is obtained at a concentration of usually 5 to 35% by weight, preferably 10 to 30% by weight.

[0127] For the polymerization of polyamic acid, any organic solvent capable of dissolving the diamine and acid dianhydride as raw materials, and the polyamic acid as the polymerization product, can be used without any particular limitation. Specific examples of organic solvents include urea-based solvents such as methylurea and N,N-dimethylethylurea; sulfone-based solvents such as dimethylsulfoxide, diphenylsulfone, and tetramethylsulfone; amide-based solvents such as N,N-dimethylacetamide, N,N-dimethylformamide, N,N'-diethylacetamide, N-methyl-2-pyrrolidone, and hexamethylphosphoric acid triamide; alkyl halide solvents such as chloroform and methylene chloride; aromatic hydrocarbon-based solvents such as benzene and toluene; ether-based solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, and p-cresol methyl ether; and ester-based solvents such as γ-butyrolactone. Among these, dimethylacetamide, dimethylformamide, or N-methylpyrrolidone is preferably used because of its excellent polymerization reactivity and solubility of polyamic acid.

[0128] <Preparation of polyimide film> Polyimide is obtained by dehydration cyclization of polyamic acid. Methods for producing a polyimide film include a method of applying a polyamic acid solution on a support in the form of a film, drying and removing the solvent, and imidizing the polyamic acid, and a method of imidizing the polyimide acid solution, dissolving the obtained polyimide resin in a solvent, applying the solution in the form of a film on a support, and drying and removing the solvent. When the solubility of the polyimide resin in the solvent is low, the former method is used. Either method can be used to make a film of a soluble polyimide. From the viewpoint of obtaining a polyimide film with few remaining impurities and high transparency, the latter method is preferred.

[0129] For imidization in a solution, a chemical imidization method is suitable in which a dehydrating agent and an imidization catalyst are added to a polyamic acid solution. The polyamic acid solution may be heated to promote the imidization process. Tertiary amines are used as the imidization catalyst. Among them, heterocyclic tertiary amines such as pyridine, picoline, quinoline, and isoquinoline are preferred. Acid anhydrides such as acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride, and trifluoroacetic anhydride are used as the dehydrating agent.

[0130] The polyimide solution obtained by imidizing polyamic acid can be used as it is as a film-forming solution, but it is preferable to first precipitate the polyimide resin as a solid. By precipitating the polyimide resin as a solid, impurities and residual monomer components generated during the polymerization of polyamic acid, as well as dehydrating agents and imidization catalysts, can be washed and removed. As a result, a polyimide film with excellent transparency and mechanical properties can be obtained.

[0131] By mixing the polyimide solution with the poor solvent, the polyimide resin is precipitated. The poor solvent is preferably a poor solvent for the polyimide resin that is miscible with the solvent in which the polyimide resin is dissolved, and examples thereof include water and alcohols. Since side reactions such as ring opening of the polyimide are unlikely to occur, alcohols such as isopropyl alcohol, 2-butyl alcohol, 2-pentyl alcohol, phenol, cyclopentyl alcohol, cyclohexyl alcohol, and t-butyl alcohol are preferred, and isopropyl alcohol is particularly preferred. Since a small amount of imidization catalyst, dehydrating agent, etc. may remain in the precipitated polyimide resin, it is preferable to wash the polyimide resin with a poor solvent. After precipitation and washing, the poor solvent is preferably removed from the polyimide resin by vacuum drying, hot air drying, etc.

[0132] The polyimide resin and the additive are dissolved in a suitable solvent to prepare a polyimide resin solution. The solvent is not particularly limited as long as it can dissolve the polyimide resin, and examples thereof include urea-based solvents, sulfone-based solvents, amide-based solvents, alkyl halide-based solvents, aromatic hydrocarbon-based solvents, ether-based solvents, etc., which are exemplified above as organic solvents used in the polymerization of polyamic acid. In addition to these, ketone-based solvents such as acetone, methyl ethyl ketone, methyl propyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, diethyl ketone, cyclopentanone, cyclohexanone, and methylcyclohexanone are also preferably used as solvents.

[0133] The polyimide resin solution may contain resin components other than polyimide and additives. Examples of additives include crosslinking agents, dyes, surfactants, leveling agents, plasticizers, fine particles, etc. The content of polyimide resin relative to 100 parts by weight of solids in the polyimide solution is preferably 60 parts by weight or more, more preferably 70 parts by weight or more, and even more preferably 80 parts by weight or more. That is, the content of polyimide resin in the polyimide film is preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more.

[0134] A polyimide film is obtained by applying a polyimide resin solution onto a support and drying and removing the solvent. It is preferable to heat the support when drying the solvent. The heating temperature is not particularly limited and is appropriately set at room temperature to about 250°C. The heating temperature may be increased stepwise. As the support, a glass substrate, a metal substrate such as SUS, a metal drum, a metal belt, a plastic film, etc. can be used. From the viewpoint of improving productivity, it is preferable to use an endless support such as a metal drum or a metal belt, or a long plastic film, etc. as the support and manufacture the film by roll-to-roll. When using a plastic film as the support, it is only necessary to appropriately select a material that is not dissolved in the solvent of the film-forming dope, and as the plastic material, polyethylene terephthalate, polycarbonate, polyacrylate, polyethylene naphthalate, etc. are used.

[0135] As a method for producing a polyimide film, the method using a solution of a soluble polyimide resin has been mainly described, but as mentioned above, a polyamic acid solution may be applied in the form of a film on a support and imidized by heating on the support. Also, the gel film after removing the solvent may be peeled off from the support and further heated to imidize.

[0136] The transparent resin film may be a single layer or a multilayer, and its structure is not particularly limited.For example, the transparent resin film layer may be a laminated transparent resin film layer having a layer other than the hard coat layer of the present invention formed on at least one surface.The layer other than the hard coat layer of the present invention may be, for example, a hard coat layer other than the hard coat layer of the present invention, a tacky adhesive layer, an antiglare layer, a polarizer-containing layer, an antireflection layer, a transparent conductive layer, an antistatic layer, etc.

[0137] The thickness of the transparent resin film is not particularly limited and can be appropriately selected, for example, from the range of 1 to 1000 μm, preferably 5 to 500 μm, more preferably 10 to 200 μm, further preferably 20 to 150 μm, and particularly preferably 30 to 80 μm. If it is thinner than 1 μm, the mechanical strength of the hard coat film may be insufficient. If it is thicker than 500 μm, the flexibility and transparency may be insufficient.

[0138] [Method of forming hard coat layer] The hard coat film of the present invention can be obtained by applying a hard coat composition to a transparent resin film and then curing the hard coat composition. The method of applying the hard coat composition is not particularly limited, and existing application methods such as roll coating such as bar coating, gravure coating, and comma coating, die coating such as slot die coating and fountain die coating, spin coating, spray coating, and dip coating can be used.

[0139] By irradiating the hard coat composition with active energy rays, an acid is generated from the photocationic polymerization initiator, and the epoxy group of the condensation product of the silane compound is ring-opened and cationic polymerized, so that curing proceeds.When the hard coat composition contains a reactive diluent, in addition to the polymerization reaction between the siloxane compounds, the polymerization reaction between the epoxy group of the siloxane compound and the reactive diluent also occurs.In addition, when the hard coat composition contains particles having reactive functional groups on the surface, the functional groups on the particle surface react with the epoxy group of the condensation product of the silane compound to form a chemical crosslink.

[0140] Examples of active energy rays irradiated during photocuring include visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays, γ-rays, and electron beams. UV light is preferred as the active energy ray because it has a high curing reaction rate and is excellent in energy efficiency. The cumulative dose of the active energy ray is, for example, 50 to 10,000 mJ / cm. 2 It may be set according to the type and amount of photocationic polymerization initiator, the thickness of the hard coat layer, etc. The curing temperature is not particularly limited, but is usually 90°C or less. If it is higher than 90°C, the equipment configuration may become complicated, or the hard coat film may become colored and the YI may increase. From the viewpoint of the mechanical strength of the obtained hard coat film, the curing temperature is preferably 30°C or more, preferably 70°C or more, and in some cases, 80°C or more is preferable. The emission dose of the active energy ray is not particularly limited, but from the viewpoint of the mechanical strength of the obtained hard coat film, it is preferably 80W / cm or more, and in some cases, 120W / cm or more is preferable. In addition, it is preferably 500W / cm or less, preferably 300W / cm or less, preferably 220W / cm or less, and in some cases, 150W / cm or less is preferable. If the emission dose is higher than 500W / cm, the hard coat film may become colored and the YI may increase.

[0141] After irradiation with active energy rays, the hard coat film is heated to 60° C. or higher. The hard coat film of the present invention is characterized in that the hard coat layer does not undergo blocking. The term "no blocking" means that the hard coat film is fixed on a horizontal table with the hard coat side facing up, a 125 μm thick PET film with an arithmetic mean surface roughness Ra of 20 nm and a maximum height Rz of 500 nm is placed on the hard coat film, and the hard coat layer is heated to 60° C. or higher. 2 This means that when a pressure of 1.0 mm is applied in the vertical direction while attempting to move the 125 μm thick PET film in the in-plane direction, the PET film slides smoothly against the hard coat film.

[0142] The silane compound condensate contained in the hard coat layer of the present invention has an alkylene group having a specific chain length between the epoxy group and the silicon atom that connects the epoxy group by chemical bond, so that the hard coat film obtained by curing shows excellent flexibility, but if the formation of a crosslinked structure by the reaction of the epoxy group after irradiation with active energy rays is not sufficient, the surface may show adhesion (tackiness). This is because the epoxy group contained in the silane compound condensate of the present invention tends to have a slower reaction rate than the alicyclic epoxy group in terms of curing by a photocationic initiator, and the reaction may not proceed sufficiently. From the viewpoint of blocking resistance, the film is heated to 60°C or higher after irradiation with active energy rays. The reaction of the unreacted epoxy group remaining in the hard coat layer is promoted by heat.

[0143] The amount of epoxy groups remaining in the hard coat layer is preferably small from the viewpoint of blocking resistance. The amount of remaining epoxy groups can be expressed as a residual epoxy group ratio (epoxy groups derived from the condensation product of the silane compound (1) before curing remaining in the cured product). The residual epoxy group ratio is expressed as a percentage of the ratio of the integral value of the two C atoms constituting the epoxy group to the integral value of the C atom adjacent to the Si atom derived from the silane compound (1) remaining in the hard coat layer divided by 2 when the hard coat layer is measured by 13C-NMR. The residual epoxy group ratio is preferably 7% or less, more preferably 5% or less, and more preferably 3% or less. When the amount of epoxy groups derived from the condensation product of the silane compound before curing in the hard coat layer is 7% or less, blocking resistance tends to be good.

[0144] The heating temperature is not particularly limited as long as it is 60° C. or higher, but is more preferably 100° C. or higher, and particularly preferably 120° C. or higher. The upper limit of the heating temperature is not particularly limited, but is preferably 200° C. or lower, more preferably 180° C. or lower, and even more preferably 150° C. or lower. If the temperature is lower than 40° C., blocking resistance may be insufficient. If the temperature is higher than 200° C., the hard coat film may be deformed.

[0145] The heating time is not particularly limited, but is preferably 10 seconds or more, preferably 1 minute or more, more preferably 2 minutes or more, and is preferably 30 days or less, preferably 7 days or less, preferably 1 day or less, preferably 60 minutes or less, and preferably 10 minutes or less. If it is shorter than 10 seconds, blocking resistance may be insufficient. If it is longer than 30 days, the hard coat film may be deformed.

[0146] The heating method is not particularly limited, and examples thereof include a batch method in which the hard-coated film is put into the heating furnace in a sheet or roll shape, and a continuous method in which the hard-coated film is continuously transported and put into the heating furnace, but the continuous method is preferred from the viewpoint of productivity. The continuous method is not particularly limited, and examples thereof include a method in which a sheet-shaped hard-coated film is transported into the heating furnace by a conveyor or the like, and a method in which a roll-shaped hard-coated film is transported into the heating furnace by a roll-to-roll method. Among them, the roll-to-roll method is preferred from the viewpoint of productivity.

[0147] The hard coat layer of the present invention may be formed on one or both sides of the transparent resin film layer.

[0148] The thickness of the hard coat layer of the present invention is preferably 0.5 μm or more, preferably 5 μm or more, preferably 10 μm or more, more preferably 20 μm or more, even more preferably 40 μm or more, and most preferably 50 μm or more. The thickness of the hard coat layer is preferably 500 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, and particularly preferably 80 μm or less. If the thickness of the hard coat layer is less than 0.1 μm, mechanical properties such as surface hardness may be insufficient. On the other hand, if the thickness of the hard coat layer is more than 500 μm, transparency and flexibility may be insufficient.

[0149] The total thickness of the hard coat film of the present invention is preferably 10 μm or more, more preferably 40 μm or more, more preferably 50 μm or more, even more preferably 60 μm or more, and most preferably 70 μm or more. The total thickness is preferably 500 μm or less, more preferably 300 μm or less, even more preferably 150 μm or less, and most preferably 120 μm or less. If the total thickness is less than 10 μm, mechanical properties such as surface hardness may be insufficient. On the other hand, if the total thickness is more than 500 μm, transparency and flexibility may be insufficient.

[0150] [Characteristics of hard coat film] The hard-coated film of the present invention has high surface hardness and flexibility, while being excellent in the balance between blocking resistance and colorless transparency. Since the hard-coated film of the present invention has excellent blocking resistance, when a long hard-coated film is wound up or when the hard-coated film is stacked on top of another hard-coated film and the hard-coated layer comes into contact with a transparent resin film, blocking does not occur, and appearance defects such as deformation, discoloration, and scratches due to blocking can be suppressed, and the hard-coated film can be suitably used as a material for displays that require high appearance properties. Here, excellent blocking resistance means that the hard-coated film is fixed on a horizontal table with the hard-coated surface facing up, and a 125 μm-thick PET film with an arithmetic mean surface roughness Ra of 20 nm and a maximum height Rz of 500 nm is placed on the hard-coated film, and the hard-coated film is subjected to a pressure of 4 kgf / cm. 2 This means that when a pressure of 10 ...

[0151] The hard coat film of the present invention is also excellent in colorless transparency. The YI value of the hard coat film of the present invention is 2.1 or less. This makes it suitable for use as a material for displays that require colorless transparency.

[0152] The hard coat film of the present invention has excellent transparency, and the total light transmittance is preferably 80% or more, more preferably 88% or more, more preferably 89% or more, and even more preferably 90% or more.

[0153] The hard coat film of the present invention also has excellent flexibility when repeatedly folded. When a repeated bending test is carried out at a radius of 3 mm using a Yuasa System Instruments U-shaped bending tester, the number of times that cracks or breakage occurs is preferably 100,000 or more.

[0154] The hard coat film of the present invention preferably has a pencil hardness of 3H or more, more preferably 4H or more, and even more preferably 5H or more, in a pencil hardness test in accordance with JIS-K5600.

[0155] The residual epoxy group ratio in the hard coat layer of the hard coat film of the present invention is preferably 7% or less, more preferably 5% or less, and more preferably 3% or less. When the epoxy group derived from the condensate of the silane compound before curing in the hard coat layer is 7% or less, blocking resistance tends to be good.

[0156] [Applications of hard coat films] The hard coat film of the present invention may have various functional layers on either or both sides thereof. Examples of the functional layers include an anti-reflection layer, an anti-glare layer, an antistatic layer, a transparent electrode, etc. A transparent adhesive layer may also be provided.

[0157] The hard coat film of the present invention has high transparency and excellent mechanical strength, and therefore can be suitably used as a cover window provided on the surface of an image display panel, a transparent substrate for a display, a transparent substrate for a touch panel, a substrate for a solar cell, etc. The hard coat film of the present invention has excellent flexibility and bending resistance in addition to transparency and mechanical strength, and therefore can be suitably used particularly as a cover window or substrate film for a curved display, a flexible display, etc. EXAMPLES

[0158] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The condensates obtained in the following synthesis examples were evaluated as follows.

[0159] <Measurement of weight average molecular weight Mw> The weight average molecular weight was measured by GPC. The GPC apparatus was a Tosoh HLC-8220GPC (column: TSKgel GMHXL x 2, TSKgel G3000H XL ,TSKgel G2000H XL ) was used, THF was used as the solvent, and the values ​​were calculated in terms of polystyrene.

[0160] <SiO 2 / 2 SiO to the body 3 / 2 Body ratio [SiO 3 / 2 body] / [SiO 2 / 2 Calculation of [body]> Using an Agilent 600MHz NMR 29 By performing Si-NMR measurement, SiO 3 / 2 Body and SiO 2 / 2 The content and proportion of [SiO 3 / 2 body] / [SiO 2 / 2 The mass ratios of the 100 mg / kg body were calculated.

[0161] <Evaluation of Residual Epoxy Groups in Silane Compound Condensates> A Bruker 400MHz NMR was used, and deuterated acetone was used as the solvent. 1 The amount of remaining epoxy groups in the condensate obtained after the reaction was calculated by H-NMR measurement.

[0162] [Synthesis of polyorganosiloxane compounds] (Synthesis Example 1) In a 200 mL flask reaction vessel equipped with a thermometer, a stirrer, and a reflux condenser, 8-glycidyloxyoctyltrimethoxysilane (Shin-Etsu Chemical Co., Ltd.; KBM-4803) (67.4 g; 220 mmol) and methanol (11.6 g) were charged and stirred uniformly. A solution of magnesium chloride (0.010 g; 0.11 mmol) dissolved in a mixture of water (11.9 g; 660 mmol) and methanol (4.7 g) was added dropwise to this mixture over 5 minutes and stirred until it became uniform. The mixture was then heated to 70°C and polycondensation reaction was carried out for 6 hours while stirring. After the reaction was completed, the mixture was devolatilized under reduced pressure and concentrated using a rotary evaporator to remove the methanol and water in the condensate. The obtained silane compound condensation product 1 was analyzed and found to have a weight average molecular weight Mw of 4,500 and29 SiO calculated by Si-NMR measurement 3 / 2 Body and SiO 2 / 2 Body ratio [SiO 3 / 2 body] / [SiO 2 / 2 Body] is 2.1, 1 The residual rate of epoxy groups calculated by H-NMR measurement was 95% or more. The content of magnesium chloride (neutral salt catalyst) calculated based on the above-mentioned charged weight was 191 ppm. The water content of the resulting condensate was measured by the Karl Fischer method and was found to be 300 ppm, indicating that the condensate contained almost no solvent.

[0163] The method for preparing the hard coat composition is as follows. [Preparation of hard coat composition] (Hard Coat Composition 1) For 100 parts by weight of the polyorganosiloxane compound obtained in Synthesis Example 1, triarylsulfonium·P(R f ) n F 6-n Hard coat composition 1 was obtained by blending 0.5 parts by weight of a 50% propylene carbonate solution of dimethylsiloxane (manufactured by San-Apro; CPI-200K) in terms of solid content and 0.125 parts by weight of a 52% xylene / isobutanol solution of polyether-modified polydimethylsiloxane (manufactured by BYK; BYK-300) as a leveling agent in terms of solid content.

[0164] The method for producing the transparent polyimide substrate is as follows. [Preparation of transparent polyimide film] (Preparation of polyamic acid solution) 2,2'-bis(trifluoromethyl)benzidine (4.48g; 14.0mmol), 3,3'-diaminodiphenylsulfone (1.49g; 6.0mmol), and N,N-dimethylformamide (DMF) (64.6g) were added to a separable flask and stirred under a nitrogen atmosphere to obtain a diamine solution. p-Phenylenebis(trimellitic acid monoester anhydride) (2.29g; 5.0mmol), 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropanoic acid dianhydride (4.44g; 10.0mmol), and 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (1.47g; 5.0mmol) were added thereto and stirred for 12 hours to obtain a polyamic acid solution.

[0165] (Imidization and isolation of polyimide resin) 28.9g of DMF and pyridine (4.75g; 60.0mmol) as an imidization catalyst were added to the above polyamic acid solution and completely dispersed, after which acetic anhydride (6.13g; 60.0mmol) was added and stirred at 80°C for 4 hours. The solution was cooled to room temperature, and while stirring, 400g of 2-propyl alcohol (IPA) was added. After stirring for about 30 minutes, suction filtration was performed using a Kiriyama funnel. The obtained solid was washed with 100g of IPA. After repeating the washing process six times, the solution was dried in a vacuum oven set at 120°C for 8 hours to obtain a polyimide resin.

[0166] (Preparation of transparent polyimide film) The polyimide resin was dissolved in dichloromethane to obtain a polyimide solution with a solid content of 10% by weight. The polyimide solution was applied to a non-alkali glass plate using a bar coater, and the solvent was removed by heating at 40°C for 60 minutes, 80°C for 30 minutes, 150°C for 30 minutes, and 170°C for 30 minutes in an air atmosphere to obtain a transparent polyimide film (substrate) 1 with a thickness of 50 μm.

[0167] The method for producing the hard coat film is as follows.

[0168] [Example 1: Preparation of hard coat film 1] The hard coat composition 1 was applied to the surface of a 50 μm thick polyimide film 1 using a bar coater so that the dry film thickness was 50 μm, and heated at 60 ° C for 2 minutes. Thereafter, using a conveying type ultraviolet irradiation device having an ultraviolet irradiation lamp (Heraeus H bulb, light emission dose after output adjustment 133 W / cm) arranged at a distance of 93 mm from the coating film, the film was conveyed at a conveying speed of 2 m / min, and ultraviolet rays were irradiated so that the accumulated light amount measured with a UV scale of Fujifilm was 1200 mJ / cm 2, and the hard coat composition was cured to obtain a hard coat film consisting of a hard coat layer and a polyimide film layer. The temperature during ultraviolet irradiation was 80 ° C. Furthermore, the hard coat film after ultraviolet irradiation was heated again at 120 ° C for 2 minutes to obtain a hard coat film 1.

[0169] (Example 2: Preparation of hard coat film 2) Hard coat film 2 was obtained in the same manner as in Example 1, except that the hard coat film after ultraviolet irradiation was heated again at 60° C. for 2 minutes.

[0170] (Comparative Example 1: Preparation of Hard Coat Film 3) Hard coat film 3 was obtained in the same manner as in Example 1, except that the hard coat film was not heated again after the ultraviolet ray irradiation.

[0171] (Comparative Example 2: Preparation of Hard Coat Film 4) Hard coat film 4 was obtained in the same manner as in Example 1, except that the emission dose after output adjustment was set to 166 W / cm and the hard coat film after ultraviolet irradiation was not heated again.

[0172] (Comparative Example 3: Preparation of Hard Coat Film 5) Hard coat film 5 was obtained in the same manner as in Example 1, except that the emission dose after output adjustment was set to 199 W / cm and the hard coat film after ultraviolet irradiation was not heated again.

[0173] (Comparative Example 4: Preparation of Hard Coat Film 6) Hard coat film 6 was obtained in the same manner as in Example 1, except that the emission dose after output adjustment was set to 216 W / cm and the hard coat film after ultraviolet irradiation was not heated again.

[0174] (Comparative Example 5: Preparation of Hard Coat Film 7) The temperature during UV irradiation is 90℃. The hard coat film was not heated again after UV irradiation. Except for the above, the same procedure as in Example 1 was carried out to obtain a hard coat film 6.

[0175] (Comparative Example 6: Preparation of Hard Coat Film 8) The temperature during ultraviolet irradiation was 40°C, the distance from the coating was 200 mm, and the light emission dose was 144 W / cm. The hard coat film was not heated again after UV irradiation. A hard coat film 8 was obtained in the same manner as in Example 1, except for the above.

[0176] (Comparative Example 7: Preparation of Hard Coat Film 9) Hard coat film 9 was obtained in the same manner as in Comparative Example 6, except that the temperature during ultraviolet irradiation was 60°C.

[0177] (Comparative Example 8: Preparation of hard coat film 10) A hard coat film 10 was obtained in the same manner as in Comparative Example 6, except that the temperature during ultraviolet irradiation was 85°C.

[0178] The physical properties of the hard coat films obtained in the Examples and Comparative Examples were evaluated as follows. The evaluation results of each Example and Comparative Example are shown in Table 1.

[0179] <Surface hardness> According to JIS K5600-5-4:1999, the pencil hardness of the surface on which the hard coat layer was formed was measured under a load of 750 g to evaluate the surface hardness.

[0180] <Total light transmittance> The measurement was performed using a haze meter HZ-V3 manufactured by Suga Test Instruments according to the methods described in JIS K7361-1: 1999 and JIS K7136: 2000. The measurement was performed using a D65 light source, and the total light transmittance was calculated as the ratio of the total transmitted light flux (parallel light component and diffuse light component) to the parallel incident light flux on the hard coat film.

[0181] <yi> Measured in transmission mode using a Suga Test Instruments SC-P colorimeter. A D65 light source was used for the measurements. The closer the YI is to 0, the higher the colorless transparency is.

[0182] <Surface roughness> The measurements were carried out using a 20x lens of a white light interference microscope, ZYGO NEWVIEW7300 manufactured by ZYGO.

[0183] <Blocking resistance> The hard coat film of the present invention was fixed on a horizontal table with the hard coat side facing up, and a 125 μm thick PET film with an arithmetic mean surface roughness Ra of 20 nm and a maximum height Rz of 500 nm was placed on top of it, and a pressure of 4 kgf / cm 2 When the film was slid while applying a pressure of 0.01 mm in the vertical direction, the hard coat film and the PET film were slid smoothly, if they slid smoothly but with some resistance, they were marked with an ◯, if they slid smoothly but with a little resistance, they were marked with an ×, if they did not slide smoothly and either went into a stick-slip state or did not slide at all, they were marked with an ◯.

[0184] <Evaluation of Residual Rate of Epoxy Groups in Cured Hard Coat Composition Containing Condensate of Silane Compound> The hard coat layer was isolated and crushed in a mortar, and then 13C-NMR measurement was performed using a VARIAN VNMRS600 to measure the amount of epoxy groups remaining in the hard coat layer after curing. The percentage of the ratio of the integral value of the two C atoms constituting the epoxy group found near 50 ppm divided by the integral value of the C atom adjacent to Si detected near 10 ppm was taken as the residual epoxy group rate (%).

[0185] <Repeated bending test> The hard-coated film was placed with the hard-coated surface facing outward in a Yuasa System Co., Ltd. U-shaped bending durability tester DMLHB, and subjected to a repeated bending test 100,000 times at a bending radius of 3 mm and a speed of 1 time per second to check for the presence or absence of cracks or breaks. The test was conducted in a constant temperature and humidity environment set at a temperature of 23°C and a humidity of 55%. If there are no cracks or breaks after the test, it indicates excellent flexibility. [Table 1]

[0186] The hard coat films of Examples 1 and 2 have a YI of 2.1 or less, and are excellent in the blocking resistance evaluation, indicating that they have an excellent balance between blocking resistance and colorless transparency. In addition, the residual epoxy group ratio is suppressed lower than that of the comparative example, indicating that the hard coat layer is cured. This hard coat film has a surface hardness of 4H or more, and is also excellent in bending resistance and light transmittance. In other words, while having high surface hardness and flexibility, it has an excellent balance between blocking resistance and colorless transparency, and can be suitably used for displays.

[0187] The hard coat film of Comparative Example 1, which was not subjected to additional heating, had a good YI but was poor in blocking resistance.

[0188] Comparative Examples 2 to 4, which were not subjected to additional heating but had high irradiation energy during ultraviolet irradiation, not only were the blocking resistance insufficient, but also had an increased YI and reduced colorless transparency.

[0189] Comparative Examples 5 to 8, in which the temperature during ultraviolet irradiation was changed without additional heating, also had insufficient blocking resistance, and some of the comparative examples also had insufficient YI and surface hardness.< / yi>

Claims

1. A hard coat film comprising a hard coat layer which is a cured product of a condensation composition of a silane compound represented by the following general formula (1) and a transparent resin film, the transparent resin film is a transparent film made of a polyester resin or a polyimide resin, The YI of the hard coat film is 2.1 or less, A hard coat film characterized in that, when the hard coat layer of the hard coat film is fixed on a horizontal table with the hard coat surface facing up, a 125 μm-thick PET film having an arithmetic mean surface roughness Ra of 20 nm and a maximum height Rz of 500 nm is placed on the hard coat film, and the 125 μm-thick PET film is moved in an in-plane direction while a pressure of 4 kgf / cm2 is applied in the vertical direction, the PET film slides smoothly against the hard coat film. (In formula (1), R 1 is a substituted or unsubstituted alkylene group having 4 to 16 carbon atoms; R 2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and R 3 is a hydrogen atom or a monovalent hydrocarbon group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, x is an integer of 2 or 3, and Y is an epoxy group represented by formula (2). 【Chemistry 1】 【Chemistry 2】

2. The hard coat film according to claim 1, characterized in that the molar ratio of the constitutional unit represented by the following general formula (3) contained in the cured product to the constitutional unit represented by the following general formula (4) [constituent unit represented by general formula (3)] / [constituent unit represented by general formula (4)] is less than 5. (In general formula (3), R 1 and Y are the same as those in the general formula (1). In the general formula (4), R 1 and Y are the same as those in formula (1), and Z is a group selected from a hydrogen atom or an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms. 【Chemistry 3】 【Chemistry 4】

3. 3. The hard coat film according to claim 1, wherein the hard coat layer contains a neutral salt catalyst in an amount of 1 ppm to 10,000 ppm.

4. 4. The hard coat film according to claim 1, wherein the hard coat layer contains an anion component of a photocationic polymerization initiator.

5. 5. The hard coat film according to claim 1, wherein the amount of epoxy groups remaining in the cured product and derived from the condensate of the silane compound before curing is 7% or less.

6. A hard coat film comprising the hard coat layer according to any one of claims 1 to 5 on at least one surface of a transparent resin film, the hard coat film having a total thickness of 10 to 500 µm and a total light transmittance of 80% or more.

7. 7. The hard coat film according to claim 6, wherein the hard coat layer has a thickness of 0.5 to 100 μm.

8. 8. The hard coat film according to claim 1, wherein the transparent resin film is a transparent film made of polyethylene terephthalate.

9. 8. The hard coat film according to claim 1, wherein the transparent resin film is a transparent film made of polyimide or polyamideimide.

10. The hard coat film according to any one of claims 1 to 7, wherein the transparent resin film is a polyimide resin having an acid dianhydride-derived structure and a diamine-derived structure, the polyimide resin contains an ester group, and is soluble in methylene chloride.

11. A display comprising the hard coat film according to any one of claims 1 to 10.

12. A method for producing a hard coat film, comprising the steps of: applying a composition containing a condensate of a silane compound represented by general formula (1) and a photocationic polymerization initiator to a transparent resin film; A step of irradiating with active energy rays; and The method includes, in this order, a step of heating to 60° C. or higher, The method for producing a hard coat film, wherein the transparent resin film is a transparent film made of a polyester resin or a polyimide resin. 1 is a substituted or unsubstituted alkylene group having 4 to 16 carbon atoms; R 2 is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and R 3 is a hydrogen atom or a monovalent hydrocarbon group selected from an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, x is an integer of 2 or 3, and Y is an epoxy group represented by general formula (2). 【Chemistry 5】 【Chemistry 6】

13. The method for producing a hard coat film according to claim 12, wherein the step of heating to 60° C. or higher comprises heating at a temperature in the range of 60° C. to 200° C.

14. The method for producing a hard coat film according to claim 12 or 13, characterized in that the molar ratio of the constitutional unit represented by the following general formula (3) contained in the cured product of the composition containing the silane compound condensate and the photocationic polymerization initiator in the hard coat film to the constitutional unit represented by the following general formula (4) [constitutional unit represented by general formula (3)] / [constitutional unit represented by general formula (4)] is less than 5. (In general formula (3), R 1 and Y are the same as those in the general formula (1). In the general formula (4), R 1 and Y are the same as those in general formula (1), and Z is a group selected from a hydrogen atom or an alkoxy group having an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 25 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms. 【Chemistry 7】 【Chemistry 8】

15. The method for producing a hard coat film according to any one of claims 12 to 14, characterized in that the hard coat film contains a neutral salt catalyst in an amount of 1 ppm to 10,000 ppm in a cured product of a composition containing a condensate of a silane compound and a photocationic polymerization initiator.

16. The method for producing a hard coat film according to any one of claims 12 to 15, wherein the hard coat film contains a cured product of a composition containing a condensate of a silane compound and a cationic photopolymerization initiator, and the cured product contains an anion component of the cationic photopolymerization initiator.

17. The method for producing a hard coat film according to any one of claims 12 to 16, wherein the epoxy group remaining in the cured product of the composition containing the silane compound condensate and the photocationic polymerization initiator in the hard coat film is 7% or less of the epoxy group of the silane compound condensate before curing.

Citation Information

Patent Citations

  • Hard coat film and image display device

    JP2015069197A

  • Stacked transparent film, window for display device, and display device

    JP2018065387A

  • Polyorganosilsesquioxane, hard coat film, adhesive sheet, and laminate

    JP2019143161A

  • Hard coating composite, and resin substrate having a hard coat layer

    WO2010110389A1

  • Photocurable and thermosetting resin composition, cured product and laminate

    WO2016098596A1